CLAYEY RAW MATERIALS FROM DOBROGEA, SOUTHERN ROMANIA, USING IN TRADITIONAL CERAMICS - Marica, S.; Ciornei, N.; Cetean, V. (Bulletin of the Geological Society of Greece, 2004)
This paper presents the results of geological and technological research on clayey and loessoid raw materials from the continental platform of the Black Sea. The loessoid clays undergo an open - cut mining under very good technical-economic conditions and are processed in a neighbouring factory. The clay deposits from the Cobadin plateau belong to the category of silt grains with the particle sizes between 0.01 and 0.03 mm. The physic-ceramic determinations proved that the clays from the Cobadin Plateau have a good shapability as raw materials. The clay preparation and working process includes: maceration in the quarry, preparation of the material by batching and mixing, shaping, compacting, finishing, hardening. The products are dried in the Kowo type natural dryers of the factory and firing takes place in a Hoffman kiln at a temperature of 950-1000°C.